Photochromic Dopamine Receptor Ligands Based on Dithienylethenes and Fulgides. Issue 54 (29th August 2017) - Lachmann, Daniel; Studte, Carolin; Männel, Barbara; Hübner, Harald; Gmeiner, Peter; König, Burkhard
Abstract: We describe the incorporation of the well‐investigated class of photochromic dithienylethenes (DTEs) and fulgides into known dopamine receptor ligands such as 1, 4‐disubstituted aromatic and hydroxybenzoxazinone piperazines as well as aminoindanes. Subtype and functional selective photochromic ligands were obtained and characterized by NMR and UV/VIS spectroscopic measurements. The photophysical properties of the DTE based dopamine ligands revealed a high fatigue resistance for the diarylmaleimides, but the ringclosure could not be accomplished in polar solvents due to a known twisted intramolecular charge transfer (TICT). Several cyclopentene‐DTEs showed high PSS, but a fast degradation by forming an irreversible byproduct. Focusing on the fulgides, high photostationary states and switching in polar solvents were possible. The compounds43, 45 and46 containing the isopropyl group showed only isomerization between the open E‐form and the closed C‐form. At a concentration of 1 nm, the cyclopentene‐DTE29 ‐open showed a more than 11‐fold higher activation of D2S, a pharmacologically important G protein‐coupled receptor, than its photochromic congener29 ‐closed. Interestingly, the fulgimide‐based pair52‐ ( E )‐open/52 ‐closed could be discovered as an alternative photoswitch with inverse activation properties exhibiting four‐fold higher activity in the closed state. Abstract : State specific G‐protein activation between the open and closed isomer of dithienylethens and fulgimides has been shown. The photophysical properties of the fulgimides exhibit high photostationary states and high fatigue resistance in aqueous buffer solutions.